Quantitative trait loci affecting intensity of violet flower colour in potato - Śliwka, Jadwiga; Brylińska, Marta; Stefańczyk, Emil; Jakuczun, Henryka; Wasilewicz-Flis, Iwona; Sołtys-Kalina, Dorota; Strzelczyk-Żyta, Danuta; Szajko, Katarzyna; Marczewski, Waldemar (Euphytica, 2017)
Anthocyanins occur in potato tuber skin and flesh, sprouts, leaves, stems and flowers. The goal of this study was to identify genomic regions and candidate gene alleles key for accumulation of anthocyanins in potato corolla in various quantities. QTL analyses were performed in two mapping populations segregating for flower colour intensity and candidate genes were identified on the basis of function and location ( chalcone isomerase , chi ; chalcone synthase , chs ) or location ( RNA - dependent RNA polymerase 1 , RDR1 ). We detected three and four QTL affecting the violet flower colour intensity using the two mapping populations, respectively. In both populations a locus F , necessary for violet flower colour, segregated and we used different approaches to differentiate the qualitative effect of this locus and to detect the genetic factors affecting the quantitative flower colour intensity. The strongest QTL and the only one common for the two mapping populations was located on chromosome V. The role of all three candidate genes, chi , chs and RDR1 , in control of flower colour intensity is supported to different extents by the performed genetic analyses. The most important QTL on chromosome V is most likely in the same position as the QTL for anthocyanin tuber flesh coloration described previously, which indicates that the natural variation in some biosynthetic and/or regulatory genes may influence anthocyanin levels in multiple tissues.